Knowledge, attitude and practice of health care workers towards COVID-19 vaccination - Sharma, Kavita; Raina, Alok; Sharma, Preeti (International Journal of Contemporary Pediatrics, 2023)
Background: A sound knowledge about vaccination against coronavirus disease-2019 (COVID-19) among health professionals is of great importance in spreading right information to general population. Aim of the study was to find the level of knowledge, attitude and practice (KAP) of health professionals towards COVID-19 vaccination. Methods: This observational study based on questionnaire done in two district hospitals of North India. Following questionnaire’s content validity, printouts of questionnaire were distributed among the healthcare workers. The assessment was made by a scoring scheme for KAP. The statistical analysis done using SPSS software and Spearman’s rank co-relation used to calculate the correlation between KAP. Results: Total 300 subjects participated in study. Social networking platform was the major source for acquiring information about COVID-19 vaccination among paramedical staff while the source of knowledge for doctors was mainly scientific websites.62.67% had moderate knowledge, 88% had positive attitude towards vaccination and 73% showed good practice. There was significant difference of KAP towards vaccine between doctors and paramedics. Conclusions: In most of health care workers level of knowledge towards COVID-19 vaccination was found to be moderate and attitude was predominantly positive. Adequate knowledge and positive of health professionals are very important for increasing the acceptance of vaccination in general population.